Organize the Role of Medical Personnel in the Care of Patients with Covid-19 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The nurses at Zangioten Hospital stressed that a comfortable working environment is paramount to ensure proper care, and they praised the availability of sufficient human resources, other facilities and equipment.